Distributed Water Demand Computation Using Remote Sensing Techniques - Rojas González, Alejandra María (2014)
The Arenal-Tempisque irrigation district is located in the lower part of the Tempisque and Bebedero basins. It is the major irrigation project of Costa Rica (59960 ha) and is divided into eight sub-districts. It has extensive agricultural activity (sugarcane, rice, watermelon, and tilapia) with high water consumption. Systematization of information is a priority issue to increase water distribution efficiency and enhance decision-making during the dry season. An example has been developed in Cañas sub-district to analyze various hydro-geospatial variables related to water demand in order to determine the water status of the region for January, February, and March, corresponding to the driest months in Guanacaste. Using GIS and remote sensing techniques, it was possible to obtain distributed water balance and water demand on farms, taking into account precipitation, temperature, evapotranspiration, and runoff. Normalized difference vegetation index (NDVI) was calculated using information extracted from LANDSAT 8 satellite images available for the study area. These were used to evaluate kc and evapotranspiration to a resolution of 30 meters. Distributed runoff was computed with the SCS method. The curve number was obtained from impermeable, vegetation, and soil proportions using LandSat images and the lineal spectrum unmixing technique for the separation. Results showed a total water deficit of 416.53 L/m2 with a standard deviation (SD) of 157.64 L/m2 during the 3 dry months.